2015
DOI: 10.1016/j.sse.2015.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Si film traps in p-channel SOI FinFETs using low temperature noise spectroscopy

Abstract: , et al.. Identification of Si film traps in p-channel SOI FinFETs using low temperature noise spectroscopy. Solid-State Electronics, Elsevier, 2015, 112, pp

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The values of + − $ were found to be 0.21 and 0.27 eV for "Peak 1" and "Peak 2," respectively. Identification of trap species, for example, hydrogen, interstitial carbon, and interstitial boron, was reported [33], in which the activation energies ranged from 0.10 to 0.44 eV. To do the same here, further investigation using more DUTs will be required.…”
Section: Low-frequency Noise Spectroscopy (Lfns)mentioning
confidence: 83%
See 1 more Smart Citation
“…The values of + − $ were found to be 0.21 and 0.27 eV for "Peak 1" and "Peak 2," respectively. Identification of trap species, for example, hydrogen, interstitial carbon, and interstitial boron, was reported [33], in which the activation energies ranged from 0.10 to 0.44 eV. To do the same here, further investigation using more DUTs will be required.…”
Section: Low-frequency Noise Spectroscopy (Lfns)mentioning
confidence: 83%
“…Using this capability, low-frequency noise measurement is commonly employed to characterize the quality of gate dielectrics [30]. In this paper, we will also demonstrate low-frequency noise spectroscopy (LFNS) [31][32][33][34], in which, by characterizing temperature-dependent noise intensities of a MOSFET, the activation energy related to electron trapping is extracted.…”
Section: Introductionmentioning
confidence: 99%
“…The values of > − $ were found to be 0.21 and 0.27 eV for "Peak 1" and "Peak 2," respectively. Identification of trap species, for example, hydrogen, interstitial carbon, and interstitial boron, was reported [32], in which the activation energies ranged from 0.10 to 0.44 eV. To do the same here, further investigation using more DUTs will be required.…”
Section: Low-frequency Noise Spectroscopy (Lfns)mentioning
confidence: 83%
“…Using this capability, low-frequency noise measurement is commonly employed to characterize the quality of gate dielectrics [29]. In this paper, we will also demonstrate low-frequency noise spectroscopy (LFNS) [30][31][32][33], in which, by characterizing temperature-dependent noise intensities of a MOSFET, the activation energy related to electron trapping is extracted.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, for the estimation of the volume trap density in conventional planar devices a correction parameter (B) value of 1/3 should be considered [7]. However, it was already demonstrated that this B parameter value is no longer a constant for multiple-gate devices [3,13]. The obtained values of the surface trap density of the identified traps, summarized in Table 2 are moderately larger compared to those previously reported for other advanced technologies [13,14].…”
Section: B Lfn As a Function Of The Temperaturementioning
confidence: 96%